Circulating Receptor Activator of Nuclear Factor kB Ligand and triglycerides are associated with progression of lower limb arterial calcification in type 2 diabetes: a prospective, observational cohort study - Olivier Bourron; Franck Phan; Mamadou Hassimiou Diallo; David Hajage; Carole-Elodie Aubert; Aurélie Carlier; Joe-Elie Salem; Christian Funck-Brentano; Salim Kemel; Philippe Cluzel; Alban Redheuil; Jean-Michel Davaine; et al. (Cardiovascular Diabetology, 2020)
Abstract Background Lower limb arterial calcification is a frequent, underestimated but serious complication of diabetes. The DIACART study is a prospective cohort study designed to evaluate the determinants of the progression of lower limb arterial calcification in 198 patients with type 2 diabetes. Methods Lower limb arterial calcification scores were determined by computed tomography at baseline and after a mean follow up of 31.20 ± 3.86 months. Serum RANKL (Receptor Activator of Nuclear factor kB Ligand) and bone remodeling, inflammatory and metabolic parameters were measured at baseline. The predictive effect of these markers on calcification progression was analyzed by a multivariate linear regression model. Results At baseline, mean ± SD and median lower limb arterial calcification scores were, 2364 ± 5613 and 527 respectively and at the end of the study, 3739 ± 6886 and 1355 respectively. Using multivariate analysis, the progression of lower limb arterial log calcification score was found to be associated with (β coefficient [slope], 95% CI, p-value) baseline log(calcification score) (1.02, 1.00–1.04, p < 0.001), triglycerides (0.11, 0.03–0.20, p = 0.007), log(RANKL) (0.07, 0.02–0.11, p = 0.016), previous ischemic cardiomyopathy (0.36, 0.15–0.57, p = 0.001), statin use (0.39, 0.06–0.72, p = 0.023) and duration of follow up (0.04, 0.01–0.06, p = 0.004). Conclusion In patients with type 2 diabetes, lower limb arterial calcification is frequent and can progress rapidly. Circulating RANKL and triglycerides are independently associated with this progression. These results open new therapeutic perspectives in peripheral diabetic calcifying arteriopathy. Trial registration NCT02431234